Α-Galacto-oligosaccharides Dose-Dependently Reduce Appetite and Decrease Inflammation in Overweight Adults. Issue 9 (15th July 2015) - Morel, Fanny B; Dai, Qiuping; Ni, Jiayi; Thomas, Doneal; Parnet, Patricia; Fança-Berthon, Pascale
Abstract: Background: Dietary fibers have been associated with a reduction in appetite and energy intake. Although a few studies suggest that nonviscous fibers can exert such effects, likely through colonic fermentation, limited data are available. Objective: The objective of this study was to determine whether α-galacto-oligosaccharides (α-GOSs), fermentable soluble fibers extracted from legumes, could reduce appetite, food intake, and inflammation in overweight subjects. Methods: In 2 single-center, double-blind, randomized, placebo-controlled trials, 88 overweight adults [50% men and 50% women; 18–60 y old; body mass index (in kg/m 2 ): 25–28] were supplemented for 14 d with tea that contained α-GOSs with different α-GOS dosages (6, 12, or 18 g α-GOSs/d), formulas (12 g α-GOSs/d with >80% of molecules with a degree of polymerization of 2, 3, or 4), or a control substance (glucose syrup). Appetite scores (5 appetite dimensions were assessed on visual analog scales during a preload test meal), food intake (test meal and 24-h food recall), and inflammatory markers [plasma lipopolysaccharide (LPS) and C-reactive protein (CRP)] were evaluated at day 0 (baseline) and day 15. Results: Changes in appetite scores from day 0 to day 15 were significantly higher after α-GOS intake, with areas under the curve for the satiety score of +121 ± 108, +218 ± 218, and +306 ± 205 score · min for 6, 12, and 18 g α-GOSs/d, respectively, and –5 ± 64 score · min for the control group. We observed dose-dependent effects that did not vary by α-GOS composition. The administration of 6, 12, or 18 g α-GOSs/d significantly and dose-dependently increased the change in energy intake from day 0 to day 15 during a test meal (–13 ± 19, –26 ± 22, and –32 ± 22 kcal, respectively; +6 ± 21 kcal for the control group). Reductions in energy intake during lunch and dinner were also higher in the α-GOS groups in the dose-effect study. At day 15, LPS was dose-dependently reduced without an association with α-GOS composition (0.16 ± 0.02, 0.12 ± 0.08, and 0.08 ± 0.05 EU/mL for 6, 12, and 18 g α-GOSs/d, respectively, and 0.06 ± 0.04 EU/mL for the control group) and CRP was significantly lower in the α-GOS groups than in the control group in the formulation-effect study. Conclusions: Consumption of α-GOSs for 14 d dose-dependently reduced appetite, food intake, and inflammation in overweight adults with no impact of α-GOS composition. Consequently, α-GOSs appear to promote long-term weight loss and mitigate metabolic disorders.